Determination of appropriate effective diffusivity for different food materials. Issue 3 (17th February 2017) - Khan, M. I. H.; Kumar, Chandan; Joardder, M. U. H.; Karim, M. A.
ABSTRACT: Effective diffusivity is the most important key parameter needed in the analysis, design, and optimization of heat and mass transfer during food drying process. In general, two types of effective diffusivities are used to develop the mathematical modeling of food drying, namely, moisture-dependent effective diffusivity (MDED) and temperature-dependent effective diffusivity (TDED). However, no study has extensively investigated which effective diffusivity is more accurate in predicting drying kinetics. The main goal of this study is to determine the appropriate effective diffusivity for predicting the drying kinetics. Drying models were developed for different fruits and vegetables based on moisture-dependent and temperature-dependent effective diffusivities. COMSOL Multiphysics, a finite element-based engineering simulation software is used to solve the coupled heat and mass transfer equations. 3D moisture profiles were developed to investigate the spatial moisture distribution during drying. Extensive experimental investigation on five types of fruits and vegetables was conducted and results were compared with the simulated results. The experiments were repeated thrice, and the average of the moisture content at each value was used for constructing the drying curves. Close agreement between experimental and simulated results validates the models developed. It was observed that the moisture profile and temperature profile in case of MDED were more closely fitted with the experimental results. For all fruits and vegetables, the moisture ratio with MDED was significantly lower than moisture ratio with TDED. This finding confirms that the MDED is more accurate for predicting kinetics in food drying. Moreover, the moisture ratio of apple was lowest whereas pear showed the highest moisture ratio. On the other hand, carrot showed a considerably lower moisture ratio compared to potato.